The influence of soil elastic modulus on lateral deflection behavior and fixity point of piles under lateral loading - Putri, Nurmalita; Effendi, Rustam (CV. Literasi Indonesia, 2026)
This research investigates the effect of soil elastic modulus variation on the lateral behavior of pile foundations, particularly focusing on the deflection profile and the depth of the fixity point, which are critical parameters in assessing the lateral capacity of deep foundations. Pile foundations, as structural elements embedded into the ground, must effectively transfer axial and lateral loads to the supporting soil layers while maintaining deformation within allowable limits. In geotechnical engineering, the elastic modulus of soil represents its stiffness and directly influences the bending moment distribution and lateral deflection behavior of embedded piles. The research was conducted through a controlled laboratory experiment using scaled physical modeling based on the principles of scaling laws. The soil used was lateritic clay from the Gunung Kupang area, characterized by fine grains and high plasticity. Variations in soil type and pile dimensions were applied to evaluate the structural response under lateral loading. Matlab software was employed for deflection visualization and fixity point estimation, leveraging its matrix-based computational environment and dynamic system modeling capabilities. The results indicate that the depth of the fixity point for test piles with diameters of 6 mm and 8 mm is significantly influenced by the soil's modulus of elasticity. In soft soil, the fixity point ranges from 13.1D - 14.2D with deflections between 0.26D - 0.44D. In medium-stiff soil, the values range from 11.3D to 12.5D with deflections of 0.25D to 0.37D, while in hard soil, the fixity point occurs at 7.5D to 9.0D with deflections of 0.21D to 0.30D. A higher modulus of elasticity significantly reduces lateral deformation and results in a shallower fixity depth, reflecting an improvement in the lateral performance of the foundation system.